Impact of Cone vs. Hetzer Repair on Postoperative Outcomes in Patients With Ebstein's Anomaly: 10-Year Experience From a Single Institution - Lou, Qi; Zou, Yiping; Wu, Jinlin; Chen, Jimei; Zhuang, Jian; Wen, Shusheng (Frontiers in Cardiovascular Medicine, 2021)
Objective: The aim of this study was to compare the early outcomes of the cone and Hetzer procedures for Ebstein’s malformation. Methods: This retrospective study included patients who underwent either cone (n=83) or Hetzer repair (n=45) with Ebstein’s malformation from January 2011 to December 2020. Results: One early death occurred in the cone group due to low cardiac output syndrome. Five cone and three Hetzer repair patients required reoperation before discharge. At discharge, the cone group had a better reduction in tricuspid valve regurgitation (TR) than the Hetzer group (74.7% vs 51.1%，p = 0.009). Two patients in the cone group and seven patients in the Hetzer group required reoperation >30 days after their initial surgery. The cone group with no/mild TR was 75.6%, and the Hetzer group was 48.9% at the time of last follow-up (p=0.010). Conclusion: Short-term outcomes of the cone repair are better than the Hetzer procedure. The cone repair should be the better option among patients with Ebstein’s malformation who need surgical intervention.